Trends in quality of screening colonoscopy in Austria - Waldmann, Elisabeth; Gessl, Irina; Sallinger, Daniela; Jeschek, Philip; Britto-Arias, Martha; Heinze, Georg; Fasching, Elisabeth; Weiss, Werner; Gschwantler, Michael; Trauner, Michael; Ferlitsch, Monika (Endoscopy, 2016)
Background and study aim: Screening colonoscopy only effectively prevents colorectal cancer if performed with high quality. The aim of this study was to analyze the detection rates of premalignant colorectal lesions in screening colonoscopies performed within a nationwide quality control program for screening colonoscopy in Austria.Methods: Data from electronic records of the screening program from its implementation in 2007 until December 2014 were analyzed in order to calculate detection rates for adenomas, advanced adenomas, polyps, and proximal lesions, and rates of cecal intubation, sedation, complications, and adequate bowel preparation. Results were evaluated to identify trends and changes in quality parameters over the 8-year study period.Results: During the study period, 301 endoscopists provided data from 159 246 screening colonoscopies. Mean age of screened individuals was 61.1 years, and 49.1 % were women. Significant increases over time were found for age- and sex-adjusted adenoma detection rates (ADRs), which increased from a mean of 22.2 % (SD 10.7 %) in 2007/2008 to 24.2 % (SD 11.6 %) in 2013/2014. On average, each endoscopist increased their individual ADR by + 1.5 percentage points per 2-year period (95 % confidence interval [CI] 0.9 – 2.2 percentage points; P < 0.01). Similarly, detection rates for proximal lesions rose from 15.8 % (SD 9.8 %) to 21.7 % (SD 13.3 %  + 2.5 percentage points per 2-year period, 95 %CI 1.9 – 3.1 percentage points; P < 0.01). ADR in men increased from 27.6 % in 2007/2008 (SD 11.1 %) to 29.2 % in 2013/2014 (SD 12.7 %; P < 0.01); ADR in women increased from 14.2 % (SD 7.1 %) in 2007/2008 to 19.0 % (SD 10.5 %) in 2013/2014 (P < 0.01). Advanced adenoma detection rates decreased during the study period, from 11.4 % (SD 9.0 %) in 2007/2008 to 7.6 % (SD 5.4 %) in 2013/2014 (P = 0.06) in men, and from 5.5 % (SD 5.3 %) in 2007/2008 to 4.0 % (SD 4.1 %) in 2013/2014 in women (P = 0.21).Conclusions: This study showed an improvement in the quality of screening colonoscopies performed within a quality assurance program in Austria between 2007 and 2014. Although, overall ADR increased significantly during the study period, there was a decrease in the rate of advanced adenoma detection.